THE INFLUENCE OF CORPORATE SOCIAL RESPONSIBILITY, TOTAL ASSET TURNOVER, AND DEFERRED TAXES ON CORPORATE FINANCIAL PERFORMANCE: THE ROLE OF COMPANY SIZE MODERATION - Mubarok, Ahmad Zakki; Haq, Saiful; Khairunisa, Vera Khairunisa; Fitriana, Amalia Indah (Universitas Muhammadiyah Tangerang, 2025)
This study addresses the growing need to understand key drivers of financial performance in manufacturing firms amid increasing demands for corporate accountability and operational efficiency. It aims to examine the effects of Corporate Social Responsibility (CSR), Total Asset Turnover (TATO), and Deferred Tax on financial performance, with Firm Size as a moderating variable, using data from manufacturing companies listed on the IDX from 2019 to 2023. Employing panel data regression analysis via EViews 9, the study uses purposive sampling to select 12 firms (60 observations). Findings reveal that TATO and deferred tax have a positive and significant impact on financial performance, while CSR does not. Firm size strengthens the effects of TATO and deferred tax but does not moderate the CSR–performance relationship. The study’s novelty lies in integrating CSR, asset efficiency, and deferred tax within a moderated model in the context of Indonesian manufacturing firms. It contributes theoretically by enriching financial performance literature and practically by guiding strategic decision-making in similar industrial settings.